Hybrid Library Service Policy Implementation at Bina Mandiri University Gorontalo - Towalu, Harson; Dunggio, Titin (CV. Publikasi Indonesia, 2023)
Bina Mandiri University Library (UBM) Gorontalo has made progress in terms of services both conventionally and digitally. However, not all academic communities are interested in using the system, in the sense that there are still library users who need a conventional or manual service system. Therefore, a Hybrid library service policy is needed that combines the two systems. This study aims to measure the level of community satisfaction as service users for the implementation of the Hybrid Library service policy at UBM Gorontalo. The method used is quantitative descriptive using the General Guideline approach for the Preparation of Community Satisfaction Survey by Permenpan RB 2017. The results showed that the implementation of the Hybrid library service policy at UBM Gorontalo as a whole, the assessment of service elements was on average assessed by respondents with good and very good categories. The dominant service element is the compatibility between the service product and the service aspect; The competence of service personnel is quite adequate and has experience in various libraries; and prompt and precise handling of complaints